A Four-Layer Odd Function Symmetrical Dual-Polarization Equilateral Right Triangle Slot Printed Broadband Directional Antenna for Wireless Lab Measurement Applications - Chang-Ju Wu; I-Fong Chen; Jwo-Shiun Sun; Chia-Mei Peng; Kang-Ling Li; Chung-Hao Huang (International Journal of Antennas and Propagation)
A four-layer odd function symmetrical dual-polarization coplanar waveguide- (CPW-) fed equilateral right triangle slot printed broadband directional antenna for wireless lab measurement applications is presented. The proposed antenna consists of two stacked perpendicular odd function symmetrical equilateral right triangle slot antenna structures with two stacked reflector ground planes. It is miniaturized, simple, and easy to be fabricated. The measured results demonstrate that the proposed antenna can achieve wide impedance bandwidth that is almost 520% for |S11| and |S22|; VSWR ≦ 3 which has implemented the operating band from 1.37 to 7.12 GHz for Global Positioning System (GPS, 1.575 GHz), Wireless Local Area Networks band (2.4 GHz and 5.8 GHz), 6 GHz unlicensed spectrum (5.925 GHz∼7.125 GHz), Long Term Evolution Upper Band (LTE, 1710–2690 MHz), and sub-6 5 G band (3.5 GHz and 4.7 GHz) applications. The measured in-band isolation performance between the two input ports |S12| ≦ −17 dB is significantly achieved, and meanwhile, the antenna radiation pattern, peak gain, and efficiency of the proposed antenna are measured as well. In the end, the radiation pattern data are compared and analyzed with simulation results.